Acute Hemolytic Reaction After Transfusion of Erythrocyte-containing Blood Components: Causes, Prevention, Clinical Cases - Ya. S. Andreyeva; O. A. Mayorova; A. Yu. Bulanov; K. S. Momotyuk; V. Yu. Zinkin; V. V. Belyakova; E. A. Vatagina (Неотложная медицинская помощь, 2021)
The article concerns the problem of studying the causes of the development of hemolytic reactions after transfusion of erythrocyte-containing blood components. The ways of preventing hemolysis as a result of blood transfusions are considered. Clinical cases are described.